Multiple tasks and neuroimaging modalities increase the likelihood of detecting covert awareness in patients with disorders of consciousness - Gibson, Raechelle M.; Fernández-Espejo, Davinia; Gonzalez-Lara, Laura E.; Kwan, Benjamin Y.; Lee, Donald H.; Owen, Adrian M.; Cruse, Damian (Frontiers in Human Neuroscience, 2014)
Minimal or inconsistent behavioural responses to command make it challenging to accurately diagnose the level of awareness of a patient with a Disorder of Consciousness (DOC). By identifying markers of mental imagery being covertly performed to command, functional neuroimaging (fMRI, EEG) has shown that some of these patients are aware despite their lack of behavioural responsiveness. We report the findings of behavioural, fMRI, and EEG approaches to detecting command-following in a group of patients with DOC. From an initial sample of 14 patients, complete data across all tasks was obtained in six cases. Behavioural evaluations were performed with the Coma Recovery Scale - Revised. Both fMRI and EEG evaluations involved the completion of previously validated mental imagery tasks - i.e., motor imagery (EEG and fMRI) and spatial navigation imagery (fMRI). One patient exhibited statistically significant evidence of motor imagery in both the fMRI and EEG tasks, despite being unable to follow commands behaviourally. Two behaviourally non-responsive patients produced appropriate activation during the spatial navigation fMRI task. However, neither of these patients successfully completed the motor imagery tasks, likely due to specific motor area damage in at least one of these cases. A further patient demonstrated command following only in the EEG motor imagery task, and two patients did not demonstrate command following in any of the behavioural, EEG, or fMRI assessments. Due to the heterogeneity of aetiology and pathology in this group, DOC patients vary in terms of their suitability for some forms of neuroimaging, the preservation of specific neural structures, and the cognitive resources that may be available to them. Assessments of a range of cognitive abilities supported by spatially-distinct brain regions and indexed by multiple neural signatures are therefore required in order to accurately characterise a patient’s level of residual cognition and awareness.